Percepción de los presos políticos sobre las condiciones jurídico-penitenciarias vividas en los establecimientos penitenciarios del Valle de Aburrá (Medellín-Colombia) (2015)
ABSTARCT: This paper aims to explore the perceptions of prisoners from the Aburrá Valley (Medellin, Colombia) on the daily conditions and the legal and correctional treatment in the space of imprisonment of the so-called political prisoners, according to 28 men and 11 women interviewed. In order to obtain the information two techniques were used: survey and focus groups. For the analysis, three variables were considered: Collective Identity; Uprooting and prisoner transfer; and prison visits and family relationships. It is concluded, based on the perceptions of the prisoners, that the physical conditions of confinement and the procedures in the prison environment involve stress, which is perceived as government retaliations against them and their social environment in order to exclude them from society, undermining their dignity and ignoring the political nature of their status as government-opponents.